"Recurrence Formula For The Impulse Response Coefficients Of The SincN FIR Filter" - Hassan, Essam (2006)
A simple recurrence formula for computing the impulse response coefficients of the SincN FIR made of a cascade of N Sinc filters each of length M is presented. The formula allows for a much lower mathematical operation compared to the previously published format and thus leads to a faster execution time and simpler circuitry.